Metode Pendidikan Islam untuk Generasi Millennial - Andi Hidayat (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2018)
Method of education is very fundamental to the achievement of learning outcomes, effective learning and will actively encourage the learners to be able to better develop their potential, ranging from intelligence, personality, attitude and skills that are useful to themselves and society.Islamic studies and human beings have a dynamism that is very fast, where Islamic religious education will be valid for all times so that whenever and whoever learned it will be able to receive the same understanding and the whole of the sources of Islamic religious education, while humans when attached as a social creature will formed a challenge for him to be able to accept the changes of the era.The method of this paper is the study of literature with descriptive approach and explorative where it can be concluded that the method of Islamic education is a method of education by working regularly and systematically and reflect on all the factors that exist to achieve the objectives of Islamic religious education, to deliver material Islamic religious education in an effective and efficient method and a dynamic approach, including hiwar methods (conversation) Qur'anic and Prophet, stories of Qur'anic and Prophet, Amtsal Qur'anic and Prophet, Exemplar, habituation and practice, ibroh and Mau'izoh, Targheeb and tarhib.